Pengembangan Alat Permainan Edukatif Ular Tangga Numerasi Untuk Meningkatkan Kemampuan Matematika Peserta Didik DI SDN 072/VII PANGINDARAN - Siti Nur Syamsiyah; Dyas Chici Kanora; Hendra Sofyan (CV. ITTC INDONESIA, 2023)
Numeracy ability is the ability to apply the concept of numbers and symbols in basic mathematics to solve problems in everyday life. In elementary school education, there are several aspects that students must master, such as cognitive, motor and psychomotor aspects. One of the abilities in the cognitive aspect that students must master is the ability to count. Numeracy is something related to managing numbers with a system that includes addition, subtraction, division and multiplication. So that mathematical skills can develop well, teachers must create a pleasant learning atmosphere, such as using the educational game Snakes and Ladders Numeracy. Snakes and Ladders Numeracy is an educational game that was developed by modifying the snakes and ladders game in general with mathematical problems. This game aims to increase the interest in learning mathematics in students at SDN 072/VII Pangindaran, in order to make it easier for students to solve a mathematics problem. The method that will be used in this research is a descriptive method, while the approach that will be used is a qualitative approach, using data collection through observation and documentation. The results of this research are that students understand the material better and can improve students' mathematical abilities. Therefore, with the educational game tool Snakes and Ladders Numeration, it can improve students' mathematical abilities and learning motivation.